Phytogenic Synthesis, Characterisation and Multifunctional Antibacterial, Antioxidant and Anti-inflammatory Activities of Zinc Oxide Nanoparticles - Prathibha, B.; Nair, Smitha; Kanmoni, V. Gnana Glory (Asian Journal of Chemistry, 2026)
In recent decades, phytochemically synthesised green nanoparticles have been extensively developed to meet a wide range of applications driven by the growing research interest in this area. Phytosynthesis of metal oxide nanoparticles was carried out using plant parts of Artocarpus altilis as the reducing agent. Zinc sulphate was used as the precursor, while aqueous extracts of leaves and stem bark served as the plant sources. The resulting zinc oxide nanoparticles, ZONP1 and ZONP2, were characterized using various physico-chemical techniques. SEM analysis shows large sized particles with irregular shapes as a result of agglomeration, a widely observed aspect in green synthesis. Both the nanoparticles show crystalline structures resembling standard wurtzite and their crystalline size is approximately 20 nm (XRD). From the FTIR spectra, the role of biomolecules in the formation of nanoparticles is confirmed and the UV-Vis results show a broad hump around 290-340 nm. Regarding the surface area, ZONP1 possesses a larger surface area of 14.12 m2/g, while ZONP2 has a larger pore size of 13.99 nm. ZONP1 shows a broad antibacterial spectrum while ZONP2 is active towards Gram-positive Bacillus cereus with an inhibition zone of 25 mm. While comparing the antioxidant capacity using the ABTS assay of ZONP1 with the larger surface area is found to show higher scavenging activity but regarding the anti-inflammatory results the ZONP2 with larger pore sizes show higher efficiency. Thus biological active chemically non-toxic environmentally safe nanoparticles are generated at minimum cost.